Capaian Kemampuan Mathematical Thinking Siswa melalui Model Comprehensive Mathematics Instructions - Delima, Nita; Kusumah, Yaya S.; Fatimah, Siti (Jurnal Elemen, 2021)
The national exam results show that students still have difficulty solving PISA standardization questions, reinforcing the reason why Indonesian students' mathematical literacy scores on PISA are still very low. This mathematical literacy is part of the mathematical thinking ability, so building it will impact students' mathematical literacy. The comprehensive mathematics instruction (CMI) model is thought to build students' mathematical thinking abilities. This study aims to describe students' mathematical thinking achievement who obtain learning with the CMI model. Besides, this study also analyzed the achievement of students' mathematical thinking through the CMI model by paying attention to the prior knowledge of mathematics (PAM). This research is a quasi-experimental study. Samples were taken purposively from the population of high school students in Subang. The results showed that the achievement of students' mathematical thinking through the CMI model differed significantly from students' mathematical thinking abilities through conventional models. The difference in the achievement of generalizing, conjecturing, and convincing abilities between students who get CMI model learning and those who get conventional model learning occurs in students with moderate PAM. Thus, the CMI model is effective for building students' mathematical thinking abilities.